2020
DOI: 10.5551/jat.51284
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Coronary Artery Calcification and Subclinical Cerebrovascular Diseases in Men: An Observational Study

Abstract: The official journal of the Japan Atherosclerosis Society and the Asian Pacific Society of Atherosclerosis and Vascular Diseases Original Article Aim: Coronary artery calcification (CAC) is an independent predictor of stroke and dementia, in which subclinical cerebrovascular diseases (SCVDs) play a vital pathogenetic role. However, few studies have described the association between CAC and SCVDs. Therefore, the aim of this study was to assess the clinical relationship between CAC and SCVDs in a healthy Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Vascular calcification is a common pathological manifestation of atherosclerosis, hypertension, diabetes mellitus, vascular injury, chronic kidney disease, and aging [ 57 ]. It is one of the important factors of the high incidence rate and mortality of cardiovascular and cerebrovascular diseases [ 58 ]. The 24-month follow-up data of this study indicated that fewer patients had CVEs, including coronary artery diseases, congestive cardiac failure, cerebrovascular accidents, and peripheral artery occlusion, in the CAC (<100) group compared to the remaining two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification is a common pathological manifestation of atherosclerosis, hypertension, diabetes mellitus, vascular injury, chronic kidney disease, and aging [ 57 ]. It is one of the important factors of the high incidence rate and mortality of cardiovascular and cerebrovascular diseases [ 58 ]. The 24-month follow-up data of this study indicated that fewer patients had CVEs, including coronary artery diseases, congestive cardiac failure, cerebrovascular accidents, and peripheral artery occlusion, in the CAC (<100) group compared to the remaining two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral or systemic atherosclerosis has been related to MRI evidence of structural brain injury and poorer cognition in many cohort studies of communityliving men and women, across various race and ethnic groups. [103][104][105][106] These effects seem to begin as early as the third and fourth decades of life and the adverse impact of early atherosclerosis on brain structure and function seems even greater than the effect of atherosclerosis later in life, [107][108][109][110][111] may be a more salient risk factor for non-AD pathology than for AD pathology, at least based on evidence from post mortem studies. 135,136 Common co-occurring factors such as obesity, diet, and physical activity also appear to be associated with neurocognitive dysfunction, which further complicates the relationship between T2D and dementia.…”
Section: Atherosclerosismentioning
confidence: 99%
“…The extent of systemic atherosclerosis tends to be correlated across various arterial beds and can be readily quantified. Cerebral or systemic atherosclerosis has been related to MRI evidence of structural brain injury and poorer cognition in many cohort studies of community‐living men and women, across various race and ethnic groups 103‐106 . These effects seem to begin as early as the third and fourth decades of life and the adverse impact of early atherosclerosis on brain structure and function seems even greater than the effect of atherosclerosis later in life, 107‐111 emphasizing that VCID accrue throughout life; that is, dementia in at least some instances is a life course disease.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Subclinical cerebrovascular diseases (SCVDs) play a vital pathogenetic role in stroke ( Oh et al, 2015 ). In 2020, a study ( Khan et al, 2020 ) evaluated the clinical relationship between CAC and SCVDs in a healthy Japanese male population. The research used Agatston method to score CAC and categorized the participants into no CAC (0), mild CAC (1–100), and moderate-to-severe CAC (>100).…”
Section: Coronary Artery Calcificationmentioning
confidence: 99%